1999
DOI: 10.1046/j.1442-2042.1999.00071.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term (4 year) efficacy and tolerability of doxazosin for the treatment of concurrent benign prostatic hyperplasia and hypertension

Abstract: Background: The a 1 -adrenoceptor antagonist doxazosin has proved successful in treating patients with concurrent benign prostatic hyperplasia (BPH) and hypertension in short-term studies. However, both conditions are chronic and may worsen over time. The aim of this study was, therefore, to examine the tolerability and efficacy of doxazosin in the long-term treatment of concurrent BPH and hypertension. Methods: This study was a longitudinal extension of earlier double-blind trials. Patients were enrolled into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…Ongoing studies with doxazosin have demonstrated good tolerability for follow-up periods currently extending to as much as 4 years (23,(31)(32)(33). The half-life of doxazosin permits once-daily dosing, and this is an important consideration for elderly patients where compliance is concerned.…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing studies with doxazosin have demonstrated good tolerability for follow-up periods currently extending to as much as 4 years (23,(31)(32)(33). The half-life of doxazosin permits once-daily dosing, and this is an important consideration for elderly patients where compliance is concerned.…”
Section: Discussionmentioning
confidence: 99%
“…29 This study demonstrated that the efficacy of doxazosin treatment for both BPH and diastolic hypertension was maintained with 4 y of continuous treatment. Analysis of data for 16 patients who completed 4 y of open-label doxazosin treatment showed significant mean reductions in sitting and standing DBP of 7.8 and 9.3 mmHg, respectively (Po0.001 for both reductions) from mean baseline values of 97.0 and 99.4 mmHg, respectively.…”
Section: Blood Pressure Effects In Hypertensive Patients With Bphmentioning
confidence: 66%
“…The discontinuation rates in the 'treated/well controlled' and Ease of using doxazosin in BPH WD Steers and RS Kirby 'untreated/normotensive' groups were 6.3 and 5.6%, respectively, compared with rates of 11.3% and 8.1% in the 'treated/poorly controlled' and 'untreated/hypertensive' groups, respectively. A double-blind, placebo-controlled, dose-response study 28 and a long-term, open-label extension of this study 29 demonstrated a significant blood pressure-lowering effect of doxazosin therapy in patients with BPH and concomitant hypertension. In the multicenter, double-blind, placebo-controlled, dose-response study, 248 patients (aged X45 y) with symptomatic BPH and mild-to-moderate hypertension (baseline sitting DBP of 90-114 mmHg) were randomized to doxazosin 2 mg (n ¼ 39), 4 mg (n ¼ 46), 8 mg (n ¼ 45), or 12 mg (n ¼ 45) or placebo (n ¼ 41) for a 14-week period, following a 2-week placebo run-in period.…”
Section: Blood Pressure Effects In Hypertensive Patients With Bphmentioning
confidence: 77%
“…Although the clinical efficacy of a 1 -adrenoceptor (AR) antagonists for the treatment of benign prostatic hyperplasia (BPH) is not disputed (Kirby and Pool, 1997;Fawzy et al, 1999;Dunn et al, 2002), their ability to maintain long-term effectiveness has only been recently investigated (Andersson et al, 2002;Bautista et al, 2003;McConnell et al, 2003). In 1994, Bendix Holme and associates, in an original clinical study on the long-term effects of doxazosin, reported that overall improvement of BPH symptoms diminished significantly over time.…”
Section: Introductionmentioning
confidence: 95%